Effect of Green Transformational Leadership and Green Knowledge on Environmental Performance with Green Creativity as Intervening Variable in Tourism Villages in DIY - Hidayati, Nida Urrahma; Effendi, Mohamad Irhas; HC, R Heru Kristanto (Westscience Press, 2024)
This study aims to examine the effect of green transformational leadership and green knowledge on environmental performance of tourism village. It also examine the mediating of green creativity on their relationship. Data was collected from 69 tourism village in the Special Region of Yogyakarta (DIY). This study used primary data collected through closed-ended questionnaires that was distributed via google forms (online) and directly (offline). The data itself were analyzed using PLS. The results show that green transformational leadership and green knowledge have positive effect on green creativity and environmental performance on tourism village. Furthermore, green creativity is also found to have mediating effect that significant between both green transformational leadership and environmental performance, also between green knowledge and environmental performance on tourism village. The main implication of this study is that tourism village need to foster both green transformational leadership and green knowledge to promote sustainability, ultimately leading to improved environmental outcomes.